2002
DOI: 10.5713/ajas.2002.932
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci Mapping for Porcine Backfat Thickness

Abstract: Microsatellite analysis and genotypingGenomic DNAs were isolated following a conventional method (Sambrook et al., 1989). Sixty five microsatellite markers on chromosomes 1, 2, 11, 13, 17 and 18 were used in the PCR amplification, of which 47 were polymorphic in the founder generation (table 1). These microsatellite markers gave a reasonable coverage of these 6 chromosomes, which belonged to one of three types of swine chromosomes. Chromosomes 1 and 2 were submetacentric, 11 was metacentric, and 13, 17 and 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…The QTL was located between the marker loci S0062 and S0120. This region concurred with the location of the back-fat thickness QTL that was found in the study by Wu et al (2001Wu et al ( , 2002 and Lee et al (2003). The QTL was in the proximity of the regions where some growth hormone pathway genes are located.…”
Section: Discussionsupporting
confidence: 84%
“…The QTL was located between the marker loci S0062 and S0120. This region concurred with the location of the back-fat thickness QTL that was found in the study by Wu et al (2001Wu et al ( , 2002 and Lee et al (2003). The QTL was in the proximity of the regions where some growth hormone pathway genes are located.…”
Section: Discussionsupporting
confidence: 84%
“…It is currently observed that IMF content is positively correlated with subcutaneous fatness. Many experiments have succeeded in identifying chromosome regions associated with backfat thickness (BFT) (Wu et al, 2001(Wu et al, , 2002. In the same studies, chromosome-wise evidence for QTL affecting BFT was found around 53cM, close to marker SW752 (Zuo et al, 2003).…”
Section: Qtl Analysismentioning
confidence: 99%
“…However, in this study, the significant associations of E36 with backfat depth traits were mainly observed in live animals (Table 4). This could have occurred if the region harboring the IFRD1 gene contained other genes that affect carcass backfat traits, such as IGFBP3 (insulin-like growth factor binding protein 3) (Wu et al 2002;Wang et al 2009) and PRKAG2 (protein kinase, AMPactivated, gamma 2 non-catalytic subunit) (Demeure et al 2004). …”
Section: Discussionmentioning
confidence: 98%